STUDY KASUS: FAKTOR-FAKTOR YANG MENYEBABKAN KESULITAN MEMBACA PERMULAAN SISWA SD SERTA UPAYA GURU DALAM MENGATASI KESULITAN MEMBACA PERMULAAN SD NEGERI TRIWIDADI - Fitri Gita Gindanti; Muhardila Fauziah (STKIP Subang, 2025)
This research aims to analyze the factors that cause elementary students' beginning reading difficulties and teachers' efforts in overcoming them, with a case study at SD Negeri Triwidadi. The research method used a qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included the principal, first grade teacher, and students. Data were analyzed using the Miles and Huberman model, including data collection, data reduction, data presentation, and conclusion drawing, with validity testing through triangulation of techniques and sources. The results showed that early reading difficulties were caused by internal and external factors. Internal factors include low motivation, concentration problems, and fear and lack of confidence. Meanwhile, external factors include lack of parental support, unsupportive environment, and less varied learning methods. To overcome this, teachers apply various strategies, such as individual guidance, repetition of material, use of interesting media, and collaboration with parents. The success of these efforts relies heavily on cooperation between teachers, students and families. This study concludes that a holistic approach, involving the roles of teachers, students and parents, is essential in overcoming early reading difficulties. Recommendations from this study are the need to increase the variety of learning methods and strengthen communication between schools and parents.